2020
DOI: 10.1071/sh18199
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental text messaging trial to improve adolescent sexual and reproductive health and smoking knowledge in Indonesia

Abstract: Background To evaluate the feasibility and acceptability of a text message intervention to improve young people’s knowledge of sexual reproductive health (SRH) and harms related to smoking in Indonesia. Methods: A quasi-experimental short message service (SMS) trial of young people aged 16–24 years receiving twice weekly SMS over a 10-week intervention period. Pre- and post-online demographic and risk behaviour surveys were used to assess changes in knowledge. Among respondents who completed both surveys, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Forty-five per cent of the respondents to data collection messages stated that they learnt something new from the text messages, and this aligns with previous studies in which participants admit that regular texts may teach them something they had not a nticipated [88]. When compared to an Indonesian smoking cessation and sex education study which reported 95% of respondents learnt something new [80], our figure appears low. In studies targeting adolescents, 83% of participants reported learning new information [70].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Forty-five per cent of the respondents to data collection messages stated that they learnt something new from the text messages, and this aligns with previous studies in which participants admit that regular texts may teach them something they had not a nticipated [88]. When compared to an Indonesian smoking cessation and sex education study which reported 95% of respondents learnt something new [80], our figure appears low. In studies targeting adolescents, 83% of participants reported learning new information [70].…”
Section: Discussionsupporting
confidence: 80%
“…A small number of participants had privacy concerns (with regards messages being seen by partners) demonstrating the sensitive nature of some of the message content. This has been mirrored in other studies wher e participants felt more comfortable with health related texts compared to sexually themed messages [80] or were worried they may be embarrassed if someone saw the content of the messages [88]. A small number of participants felt that the messages were not appropriate to them -i.e.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, it was also reported that millions of. adolescents have encountered challenges on reproductive health and sexual activity, not limited to a high rate of unsafe abortion, contraception issues, and unintended pregnancy [2], [3]. The study also reported that almost 49.8% of adolescents had no idea about the use of birth control [1].…”
Section: Introductionmentioning
confidence: 94%
“…It is also known where psychological stressors come with the diversity and density of the cities [9], [10]. In urban environments, it is usually easy to find places that sell alcoholic and smoke, which affect the risk for adolescents to engage in drugs and sexual risk behavior [3], [11], [12]. Nevertheless, a developing body of investigation proposes that neighborhood characteristics impact well-being results and behaviors, being counted as sexual behavior.…”
Section: Introductionmentioning
confidence: 99%